Variability of maximum oxygen consumption measurement in various metabolic systems - Babineau, C.; Leger, L.; Long, A.; Bosquet, L. (The Journal of Strength and Conditioning Research, 1999)
Although at one time or another most laboratories experience measurement errors in maximum oxygen consumption (o2max), this issue is rarely addressed in scientific literature. Some national certification bodies that supervise the accreditation process accept a variance in aerobic capacity measurement of 4% or 2 to 3 ml·kg1·min1 between various metabolic systems. The results obtained in 3 succesive experiments show the importance of more frequent verifications and a closer control when calibrating equipment, particularly with automated systems. Indeed, after conducting routine o2max tests in 2 independent laboratories during complementary work (study A), the following results were obtained: time to exhaustion (laboratory 1: 16:02; laboratory 2: 15:49 min:s) and maximal speed (laboratory 1: 4.98; laboratory 2: 4.85 m·s1) favored laboratory 1, whereas o2max (laboratory 1: 59.7; laboratory 2: 68.7 ml·kg1·min1) was significantly higher in laboratory 2. Following these observations, study B (within subjects) and study C (within metabolic systems) were instigated to further explore this issue. Discrepancies in o2 and o2max of 10-15% or 5-10 ml·kg1·min1 were observed between and within subjects for submaximal and maximal workloads. A detailed analysis of collected variables revealed that the ventilation measure seemed to be the key parameter involved, although other parameters cannot be excluded. This stresses the need to perform regular and rigorous calibration of each component of the system and to cross-validate the system or conduct multiple trials with some subjects. It appears that the calibration and verification of metabolic systems, particularly ventilatory apparatus, for moderately active adults and high-performance athletes is of paramount importance.